2013
DOI: 10.1017/s1368980012005514
|View full text |Cite
|
Sign up to set email alerts
|

Association of beverage consumption with obesity in Mexican American children

Abstract: Objective To determine the association of beverage consumption with obesity in Mexican American school-aged children. Design Cross-sectional study using the baseline data from a cohort study. Mothers and children answered questions about the frequency and quantity of the child’s consumption of soda, diet soda, other sugar-sweetened beverages, 100% fruit juice, milk and water. The questions were adapted from the Youth/Adolescent FFQ. Children were weighed and measured. Data were collected on the following pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…We found that nearly all articles included non-White children. Some articles focused exclusively on minority children, including 20 that focused specifically on African American children (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71); 19 that focused on Hispanic children (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90); six that focused on Native American, Alaskan Native or American Indian children (91)(92)(93)(94)(95)(96); and one that focused on Asian or Asian-American children (97). These articles may serve as references to evaluators wishing to assess beverage consumption in these populations, although evaluators should attend to whether the assessment methods described in these articles have been ...…”
Section: Discussionmentioning
confidence: 99%
“…We found that nearly all articles included non-White children. Some articles focused exclusively on minority children, including 20 that focused specifically on African American children (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71); 19 that focused on Hispanic children (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90); six that focused on Native American, Alaskan Native or American Indian children (91)(92)(93)(94)(95)(96); and one that focused on Asian or Asian-American children (97). These articles may serve as references to evaluators wishing to assess beverage consumption in these populations, although evaluators should attend to whether the assessment methods described in these articles have been ...…”
Section: Discussionmentioning
confidence: 99%
“…43 In addition, we observed that higher levels of monitoring, limit setting SS, and limit setting SM were inversely associated with frequency of SSB availability; thus, parents who reported engagement in higher levels of these practices had significantly reduced odds of reporting usually/always serving SSBs at meals, compared to never/sometimes. SSBs are a major source of added sugar and excess calories among low-income children, [44][45][46] and reduction of SSB availability in the home may improve children's dietary quality and body weight. 47 De Coen and colleagues 48 observed that mean soft drink consumption of children from high SES was 58% times less than children of low SES, and that this relationship was mediated by availability/ accessibility of soft drinks at home.…”
Section: Discussionmentioning
confidence: 99%
“…Increased SSB intake in adolescents was associated with higher systolic blood pressure, a risk factor for hypertension and cardiovascular disease (Nguyen, Choi, Lustig, & Hsu, 2009). Additionally, SSB intake has been associated with increased body weight in adolescents (Beck, Tschann, Butte, Penilla, & Greenspan, 2013; Berkey, Rockett, Field, Gillman, & Colditz, 2004; Ebbeling et al, 2006), with a dose responsive relationship between SSB intake and obesity risk in adolescents who consume four or more eight ounce servings per week (Martin-Calvo et al, 2014). Longitudinal data has shown that a single serving of SSB per day at age 15 years increased body mass index (BMI) and waist circumference over six years (Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%